2022
DOI: 10.3390/md20080483
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Effects of Krill Oil on Obesity and Obesity-Induced Metabolic Syndromes in High-Fat Diet-Fed Mice

Abstract: Obesity increases the risks of metabolic syndromes including nonalcoholic fatty liver disease (NAFLD), diabetic dyslipidemia, and chronic kidney disease. Dietary krill oil (KO) has shown antioxidant and anti-inflammatory properties, thereby being a therapeutic potential for obesity-induced metabolic syndromes. Thus, the effects of KO on lipid metabolic alteration were examined in a high-fat diet (HFD)-fed mice model. The HFD model (n = 10 per group) received an oral gavage with distilled water as a control, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
11
1
Order By: Relevance
“…Additionally, it has been demonstrated that insulin resistance is associated with defects in PI3K/Akt pathway [48] . In the current study, KO treatment for 6 weeks did not ameliorate insulin resistance in HFD-induced obese mice notably, which is inconsistent with other studies [26,49] . This conflicting evidence might be due to the varying intervention time and doses of KO in our and other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been demonstrated that insulin resistance is associated with defects in PI3K/Akt pathway [48] . In the current study, KO treatment for 6 weeks did not ameliorate insulin resistance in HFD-induced obese mice notably, which is inconsistent with other studies [26,49] . This conflicting evidence might be due to the varying intervention time and doses of KO in our and other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it has been demonstrated that the presence of astaxanthin in KO increases the stability of n-3 LCPUFAs and protects them against oxidation that may lead to better health outcomes [22] . In recent decades, several studies have shown that KO has therapeutic potential in several diseases such as inflammation, acute liver injury, hyperlipidemia, obesity and diabetic complications [23][24][25][26][27][28] . A recent study reported that KO supplementation improved muscle function and size in healthy older adults [29] .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, KO has been recognized as a marine-derived natural substance with significant activation of nuclear factor E2-related factor 2 (Nrf2) transferase and potent antioxidant properties, making it a promising raw material for health functional foods with natural antioxidant benefits [ 16 , 17 ]. Although previous research on human immortalized keratinocyte lines and NC/Nga mice has suggested the potential benefits of KO in terms of antioxidants and anti-inflammatory effects [ 11 , 18 ], there is a lack of direct and detailed research on KO’s role in improving skin wrinkles and moisturization.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation, a secondary evaporation and filtration were conducted to produce the final product, KO. The KO composition included 51.2% (wt/wt) phospholipids, comprising 44.9% phosphatidylcholine, 3.6% 1-palmitoyl-2-hydroxy-glycero-3-phosphocholine, 2.1% phosphatidylethanolamine, and 0.6% N-Acyl-phosphatidylethanolamine [ 17 ]. Additionally, EPA and DHA contents were analyzed in the KO.…”
Section: Methodsmentioning
confidence: 99%
“…KO has been reported to have anti-inflammatory, anti-oxidative, and anti-fibrotic activities in mouse models of diabetic complications [ 11 , 12 , 27 ]. We previously found that KO could inhibit DM-induced cardiac and renal inflammation and fibrosis, preventing diabetic cardiomyopathy and nephropathy in a mouse model of T2DM [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%